Diagnosing The most common sports injuries among the students ofFaculty of Physical Educationin An-NajahNational University - Sameer Mahmoud Rashed, Mosab; hosnihassanAlatrash, Mahmoud; Abdulhadi Mahmoud E'mar, Maryam; Khaled salem al-bqaei, Ibrahem (sports creativity, 2025)
This study aimed to identify the most common sports injuries among students of the Faculty of Physical Education at An-Najah National University, as well as to identify the most common and most exposed areas of sports injuries among students and the most common causes. That lead to sports injuries and the most practical courses that occur among students of the Faculty of Physical Education at An-Najah National University, in addition to identifying statistical differences of statistical significance for the number of injuries among students of the Faculty of Physical Education at An-Najah National University. Variables (academic level, gender), the researcher used the descriptive method in the study, and used the questionnaire as a tool to collect data, and the study sample consists of (475) students, who were randomly chosen, and enabling the Statistical Packages Program (SPSS,26) to analyze the results, and the results numbers of the most injuries that students are exposed to are Muscle strain injury, and that the most anatomical body sites exposed to sports injuries among students were the area of the combs of the hand followed by the knee joint, that the highest rate of injuries suffered by students in the course of physical preparation, and that the most leading causes of sports injuries to them is bad weather conditions, as they are the results The presence of statistically significant differences at the level of significance (0.05 ≥α) causes sports injuries in the Faculty of Physical Education, An-Najah University on the variable of School years, between first-year and second-year students and in favor of the first-year application, and there are differences related to statistical significance at the level of significance ((0.05 ≥α)) between third-year and second-year students and for third-year students, and there are statistically significant differences at the level of Significance (0.05 ≥α) between second and fourth year students and for the benefit of second year students, and there are statistically significant differences at the level of significance (0.05 ≥α) for sports injuries in the College of Physical Education - An-Najah University in accordance with the gender variable and in favor of males, and in light of the results The study recommended the researchers to pay attention to the good and proper warm-up of all working muscles, and to follow the students during practical lessons by the teacher and to guide them, which occurs occurring